Peningkatan Akhlak Berpakaian Dan Berhias Siswi Melalui Pemahaman Fiqih Wanita Di MAN Kota Pasuruan - Munir, Miftakhul; Niswati, Suci (LPPM Sekolah Tinggi Agama Islam Al Azhar, 2021)
Increasing the character of dress and decoration of students through the understanding of fiqh of women in MAN Pasuruan City, MAN Pasuruan City students use uniforms in an Islamic way, at least the hair and limbs are not visible apart from the hands and face. Meanwhile, the efforts of PAI teachers in improving the dress and decorating morals of students through the understanding of women's fiqh in Pasuruan City MAN, namely trying their best, especially female students always cover their genitals not only at school but outside school, they must always cover their genitals, if women have their genitals all over their faces and palms. . Then many of them have followed recommendations to cover their genitals, especially from religious teachers. Whereas the method used by Islamic Education teachers in improving the dress and decorating morals of students through the understanding of women's fiqh in MAN Pasuruan City is the most important method is the habituation method, so if you meet students there are things that are not good seen will be given directions, lecture methods and discussion, and methods of providing motivation.